2013
DOI: 10.1186/1479-5876-11-66
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition, a new inducer for arterial calcification in hemodialysis patients?

Abstract: BackgroundArterial calcification is a significant cardiovascular risk factor in hemodialysis patients. A series of factors are involved in the process of arterial calcification; however, the relationship between malnutrition and arterial calcification is still unclear.Methods68 hemodialysis patients were enrolled in this study. Nutrition status was evaluated using modified quantitative subjective global assessment (MQSGA). Related serum biochemical parameters were measured. And the radial artery samples were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
2
15
2
Order By: Relevance
“…Although lower total cholesterol levels were observed in malnurished geriatric MHD patients, this study found no statically significant correlation between MQSGA scores and cholesterol levels [17, 18]. Serum phosphorus levels were found low in elderly patients and this was considered as related with poor nutritional intake.…”
Section: Discussionmentioning
confidence: 70%
“…Although lower total cholesterol levels were observed in malnurished geriatric MHD patients, this study found no statically significant correlation between MQSGA scores and cholesterol levels [17, 18]. Serum phosphorus levels were found low in elderly patients and this was considered as related with poor nutritional intake.…”
Section: Discussionmentioning
confidence: 70%
“…It is found that about 92% young ESRD patients had coronary artery calcification (CAC) (78). In hemodialysis patients, we observed that nearly 46% of them suffered different degree of radial calcification (110). In addition, we also found that the calcified depositions were mainly located in the medial layer of the radial arteries, leading to thickening of the medial layer (110).…”
Section: Ac In Ckdmentioning
confidence: 74%
“…However, our previous study found an increase of MGP and BMP2 expressions in the calcified areas of radial arteries in malnourished ESRD patients (110). This may be attributed to the lower ratio of MGP/BMP2 or the uncarboxylated form of MGP.…”
Section: The Possible Mechanisms For Mics-induced Ac In Ckdmentioning
confidence: 75%
See 2 more Smart Citations